Dictionary Article as Text in Lexicology Instruction - Bojana Milosavljević (University of Belgrade, Teacher Education Faculty, 2020)
The paper presents the possibilities of using dictionary articles from our descriptive monolingual dictionaries as texts for teaching lexicology at academic courses of teacher training faculties. The starting point of the paper is that literary texts are traditionally used in teaching languages, while other types of texts (non-literary texts) are less frequently used, which, in turn, affects students'reading literacy. The main part of the paper focuses on the qualitative analysis of the selected dictionary articles from our descriptive monolingual dictionaries, with a special emphasis on using a dictionary article in teaching lexicology as an 1) introductory text, 2) text used for identifying lexical phenomena, 3) text used for practising lexical phenomena, and 4) text as a part of the knowledge assessment test. Based on our analysis, we concluded that using dictionary articles in teaching lexicology may entail multiple benefits - acquiring the knowledge of lexicology, enriching one's vocabulary, developing language culture, but also developing lexicological knowledge, skills, and habits, which fosters preservice primary school teachers' functional literacy.